Effect of garlic powder supplementation on rumen microbiota and histology, and blood metabolites in Barki lambs - Alaa Emara Rabee; Afaf A. El Shereef; Mahmoud S. Nassar; Mohammed A. H. El-Rayes; Rasha S. Mohammed; Salah Abo Bakr (BMC Veterinary Research)
Abstract Background Garlic (Allium sativum) contains different bioactive compounds that have antimicrobial activities, which might modify rumen fermentation and improve animal performance. This study investigated the effect of garlic powder supplementation on growth performance, rumen fermentation and microbiota, blood metabolites, and immunity in Barki lambs. Twelve Barki lambs were assigned into two dietary treatments (n = 6): basal diet (control group) or basal diet supplemented with garlic powder as 2% of dry matter (DM) intake. The basal diet consisted of alfalfa hay and a concentrate feed mixture. Results The results showed that garlic supplementation enhanced the growth performance, blood immunoglobulins IgG and IgA, rumen pH, and the proportions of propionic, isobutyric, and isovaleric (P < 0.05). Moreover, the rumen ammonia, predicted methane, and microbial alpha diversity were declined due to garlic supplementation (P < 0.05). Principal Co-ordinate analysis (PCoA) revealed that microbial communities were clustered according to dietary treatments. The bacterial community was dominated by phyla Bacteroidota and Firmicutes. The supplementation improved the relative abundance of the family Ruminococcaceae, genus Prevotella and Butyrivibrio which were correlated positively with growth performance and blood immunity (P < 0.05). Conclusions The results explain that garlic powder could modify rumen microbiota to improve rumen fermentation, immunity, and growth performance in growing lambs.